Reflexivity in Counterspaces Fieldwork. Issue 3 (13th October 2017) - Case, Andrew D.
Abstract: Reflexivity is an important tool for navigating ethically important moments in fieldwork. It may be particularly useful in situations where the researcher has the potential to undermine the conduct of the study and/or the well‐being‐enhancing role of counterspaces. In this article, I explore my use of reflexivity to traverse ethically important moments I encountered while investigating a counterspace for African‐American youth who had been incarcerated. The ethical challenge concerned whether and how to continue this study in light of realizing that I held implicit biases toward the research participants. I describe my process for arriving at a decision and propose key considerations for the use of reflexivity in supporting ethical fieldwork within counterspaces. Highlights: Unique and consequential ethical challenges can emerge in the context of counterspaces fieldwork. Reflexivity has utility in successfully navigating these challenges. It is critical that we foster reflexivity in community psychology training.